Pengaruh Pemberian Makanan Tambahan Pemulihan Terhadap Perubahan Berat Badan Balita Bawah Garis Merah Kecacingan Di Wilayah Puskesmas Klambu Kabupaten Grobogan - Dyah Heru Retnowati; Agustin Syamsianah; Erma Handarsari (Jurnal Gizi, 2015)
The toddler years are the first five-year period in a child's life every human being A golden age is very important , especially physical growth . At this time 90 % of individual brain cells grow and thrive . When the golden age of children neglected , it will be a problem for the toddler, now and in the future.The research is analytical research with Pre - experimental research method and a one- group pre - test post - test design . This study aims are to determine the effect of supplementary feeding on recovery changes in weight BGM worm at the area of Kelambu health center at Grobogan regency . Samples were taken by means of saturation sampling , as the sample of all infants BGM worm.There is a difference in weight before and after the administration of PMT – P (p = 0.000) , there is a correlation between energy intake with changes of body weight (p = 0.000), and there is a correlation between proteins intake with changes of body weight,(p = 0.000).Keywords :PMT-P, changes of baody weight, BGM worm